2017
DOI: 10.1002/admi.201701007
|View full text |Cite
|
Sign up to set email alerts
|

Injection Current Barrier Formation for RbF Postdeposition‐Treated Cu(In,Ga)Se2‐Based Solar Cells

Abstract: Among the thin‐film solar cell technologies, Cu(In,Ga)Se2‐based solar cells demonstrate the highest efficiencies, where the recent boost in efficiency is triggered by a KF postdeposition treatment (PDT). In this contribution, Cu(In,Ga)Se2‐based solar cells are fabricated using RbF PDTs after absorber layer growth with varying substrate and RbF source temperature. The electronic charge transport properties of the solar cell devices are investigated using temperature‐dependent current–voltage analysis and admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 29 publications
7
75
0
Order By: Relevance
“…This high performance was achieved by incorporating KF, RbF, or CsF into the absorber layer via PDT. Regarding the effects of alkali fluoride PDT on device parameters, an increase in the open‐circuit voltage ( V oc ) has been observed consistently, whereas short‐circuit current ( J sc ) and fill factor (FF) present an inconsistent trend in different contributions . For the context of this work, we note that some publications have reported the presence of a barrier for the bucking and/or photo current, resulting for instance in a rollover of the current–voltage ( J–V ) characteristics or a crossover between dark and light J–V curves after PDT …”
Section: Introductionmentioning
confidence: 68%
“…This high performance was achieved by incorporating KF, RbF, or CsF into the absorber layer via PDT. Regarding the effects of alkali fluoride PDT on device parameters, an increase in the open‐circuit voltage ( V oc ) has been observed consistently, whereas short‐circuit current ( J sc ) and fill factor (FF) present an inconsistent trend in different contributions . For the context of this work, we note that some publications have reported the presence of a barrier for the bucking and/or photo current, resulting for instance in a rollover of the current–voltage ( J–V ) characteristics or a crossover between dark and light J–V curves after PDT …”
Section: Introductionmentioning
confidence: 68%
“…In fact, on an RbF‐treated low‐temperature absorber, a reduction of the measured barrier was observed after etching the treated film and supposedly reducing the thickness of a Rb‐In‐Se layer, see Figure S1 in the Supporting Information and ref. . However, our DFT modeling of band offsets for idealized model interfaces between CuInSe 2 and KInSe 2 , RbInSe 2 , and CsInSe 2 shows actually downward shifts of the conduction band edge, see Figure S2 in the Supporting Information.…”
Section: Effects Of Post‐deposition Treatment With Heavy Alkalismentioning
confidence: 78%
“…By contrast, Igalson et al reported on a correlation between the N1 signature and blocking of the diode current in forward bias, which they attributed to Fermi level pinning at the CIGS/buffer interface at the front of the device. Recently, we demonstrated that excessive RbF treatment leads to modifications of the CIGS/buffer interface, which affect the N1 signature observed in admittance spectroscopy . We further demonstrated that bias‐dependent and illumination‐dependent impedance spectra of CIGS solar cells suggest a depleted buffer layer but are difficult to reconcile with deep defects as origin of the N1 signature .…”
Section: Introductionmentioning
confidence: 87%
“…Recently, we demonstrated that excessive RbF treatment leads to modifications of the CIGS/buffer interface, which affect the N1 signature observed in admittance spectroscopy. 21 We further demonstrated that bias-dependent and illuminationdependent impedance spectra of CIGS solar cells suggest a depleted buffer layer but are difficult to reconcile with deep defects as origin of the N1 signature. 22 However, both different back electrodes 23 and different buffer layer stacks 24 at the front of the device were reported to modify the admittance spectrum, and the main capacitance step of all devices was found to agree with the N1 signature.…”
mentioning
confidence: 89%